2003
DOI: 10.1111/j.1651-2227.2003.tb02472.x
|View full text |Cite
|
Sign up to set email alerts
|

Clinical onset and diagnosis of eating disorders in premenarcheal girls is preceded by inadequate weight gain and growth retardation

Abstract: Aim: To study growth and weight changes before the presentation of an eating disorder (ED) with premenarcheal onset. Methods: Growth charts from the school health services were obtained for 45 girls assessed during the period 1990–2000 at Uppsala University Children's Hospital. Measurements of weight and height from the charts and at presentation were recalculated into standard deviation scores (SDS). Results: At their maximal weight the girls were 12.5 ±1.7 (mean ± SE) y old. They were then lighter, shorter a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0
3

Year Published

2005
2005
2017
2017

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(23 citation statements)
references
References 21 publications
1
19
0
3
Order By: Relevance
“…In growing teenagers, this is an important issue because a weight, which at a certain age is average, may later represent underweight due to the absence of expected weight gain. The DSM-IV weight criterion for AN may thus be fulfilled if a teenager maintains constant weight over a period when weight gain is expected as part of normal growth (Swenne & Thurfjell, 2003). Premorbid weight history in teenagers with ED therefore must include not only top weight but also when it was reached.…”
Section: Resultsmentioning
confidence: 99%
“…In growing teenagers, this is an important issue because a weight, which at a certain age is average, may later represent underweight due to the absence of expected weight gain. The DSM-IV weight criterion for AN may thus be fulfilled if a teenager maintains constant weight over a period when weight gain is expected as part of normal growth (Swenne & Thurfjell, 2003). Premorbid weight history in teenagers with ED therefore must include not only top weight but also when it was reached.…”
Section: Resultsmentioning
confidence: 99%
“…In a majority of the patients, weight loss starts from a weight above average, and onset of weight loss is reasonably distinct and occurs at an age when only little further growth in stature can be expected (Nielsen, 1985;Swenne, 2001). However, in younger patients who have not yet completed puberty, onset may be insidious and frank weight loss may be preceded by a long period of inadequate weight gain and growth retardation (de Monléon et al, 1998;Jeammet, Hurvy, Rabreau, Piquard-Gauva, & Flavigny, 1984;Modan-Moses et al, 2003;Russel, 1985;Swenne & Thurfjell, 2003). These patients are of an age when considerable further growth should be expected and it is therefore of concern when they present with stunting of growth and delayed development (Abadie, de Tournemire, & Alvin, 2003;Danziger, Mukamel, Zeharia, Dinari, & Mimouni, 1994;de Monléon et al, 1998;Gowers, Crisp, Joughin, & Bhat, 1991;Modan-Moses et al, 2003;Pfeiffer, Lucas, & Ilstrup, 1986;Root & Powers, 1983;Russel, 1985;Swenne & Thurfjell, 2003).…”
Section: Introductionmentioning
confidence: 97%
“…Results from a 2005 study inquiring about the attitudinal differences in body image between patients with anorexia nervosa and bulimia nervosa showed that individuals with bulimia reported more body image dissatisfaction than those diagnosed with anorexia (Swenne & Thurfjell, 2003). Using this concept, a future study can select participants with an Eating Disorder diagnosis and seek to determine different feelings toward menarche between the diagnoses.…”
Section: Future Directionmentioning
confidence: 99%